Fauna and Biodiversity Investigations of Fleas Caught in Livestock Farms: Neka City, Mazandaran Province, Iran - Golnesa Bagheri; Nasibeh Hosseini-Vasoukolaei; Farzad Motevalli Haghi; Ahmadali Enayati; Mahmoud Fazeli Dinan; Hasan Nikookar; Farzaneh Sahraee (تحقیقات سلامت در جامعه)
Introduction and purpose: Fleas are ectoparasites of birds and mammals. In addition to causing harassment due to their bites, these insects transmit some diseases, such as plague, endemic typhus, and tularemia, to humans. The present study aimed to identify the species and biodiversity of important fleas in Neka City (Mazandaran Province, Iran). The present research followed a descriptive-analytical approach. Methods: The sampling was performed for one year, from April to March 2022, in the rural areas of Neka City. In this study, 15 villages were randomly selected according to the geographic location of the north, south, east, west, and center. Different methods, including hand catch, human bait, and spreading white cloth, were employed to collect fleas. The collected samples were preserved in closed tubes containing 70% alcohol. After clarification and mounting in the laboratory, they were identified using validated identification keys. Results: A total of 2600 fleas were caught in this study, involving Ctenocephalides canis (30.93%), Ctenocephalides felis (57.54%), and Pulex irritans (11.53%) species. Among them, 33.12% were male, and 66.89% were female. The dominant species among the caught fleas was Ctenocephalides felis, and the majority of the collected fleas were caught in the Estakhr Posht village. Furthermore, the highest number of fleas caught was associated with the mountainous climate and occurred during spring. Conclusion: The results revealed that Ctenoscephalides felis is the dominant and most abundant species in Neka City, Iran, which can be considered a health concern. Therefore, their presence and frequency should be considered a serious issue, and appropriate control measures should be made.